A Psychological Analysis of Paranoid Personality Disorder in William Shakespeare’s Drama The Winter’s Tale - Perveen Sonia Mahid; M Manugeren; Hidayati Hidayati (Universitas Islam Sumatera Utara, 2026)
This research analyses Paranoid Personality Disorder (PPD) symptoms in King Leontes, the central character of William Shakespeare's drama The Winter's Tale. While previous studies have examined Shakespearean jealousy from literary perspectives, limited attention has been paid to clinical psychological analysis using established diagnostic frameworks. This study addresses that gap. Using a descriptive qualitative method, this research identifies four PPD symptoms in Leontes' behaviour: jealousy, grudge, doubting the loyalty of others, and sensitivity to criticism. The theoretical framework combines Emil Kraepelin's classification of paranoia, Sigmund Freud's psychoanalytic theory of projection, and Carl Jung's concept of the collective unconscious. The findings demonstrate that Leontes exhibits all four symptoms. His excessive jealousy toward Queen Hermione, explosive anger, loss of trust in his closest advisors, and extreme sensitivity to criticism drive him to order Hermione's imprisonment, banish his newborn daughter Perdita, and attempt to poison his best friend Polixenes. This research contributes to both literary studies and clinical psychology by demonstrating that Shakespeare's characterization of Leontes is a realistic depiction of a personality disorder, not merely a plot device. By applying Kraepelin's, Freud's, and Jung's theories to a classical literary character, this study bridges the gap between clinical psychology and literary analysis, offering a fresh perspective on The Winter's Tale that moves from literary themes of